History's Ghost Haunting Vince Gilligan's New Mexico: Genre, Myth, and the New Western History in Breaking Bad. Issue 2 (3rd April 2019) - Bernhardt, Mark
ABSTRACT: Breaking Bad 's creator and producer, Vince Gilligan, depicts how the past shapes the present in ways to which the show's characters often seem blind, specifically regarding interracial violence, white occupation of the West, how conquest negatively impacted women's lives, and the retention and appropriation of culture.